Study The Effect of Conditions of The Electro Spinning Cabin (Humidity) on Electro-spun PolyVinyl Alcohol (PVA) Nano-fibers - Alswid, Samara; Issa, Manal (Al-Nahrain Journal for Engineering Sciences, 2017)
Electrospinning is a simple and highly versatile method for generating ultrathin fibers (mainly polymers) with diameters ranging from a few micrometres to tens of nanometres. This technique has attracted tremendous recent interest in both academia and industry, owing to its unique ability to produce ultrafine fibers of different materials in various fibrous assemblies. Electrospinning is a process that uses an electric potential to overcome the surface tension of a solution to produce an ultra-fine jet, which elongates, thins and solidifies as it travels through the electric field to a collector.. In this research, we studied the effect of conditions of the cabin “specifically humidity” on the diameter of nanofibers manufactured by electrospinning. We used Polyvinyl alcohol (PVA) polymeric solution with weight concentration of 10%, voltage 20 kv, under different values of relative humidity. Fiber morphology and fiber diameter were determined using scanning electron microscope, and measuring the fiber diameter by using image j program. It was found that the diameter of the fibers increased with increasing the relative humidity within our studying area .